A NATURAL TOUCH IN FASHION: STEAM ECOPRINTS WITH LEAVES AND FLOWERS at SMP NEGERI 6 BANDA ACEH - Zahara, Meutia; Helmanda, Cut Mawar; Nazariah, Nazariah; Anshari, Badrun Al; Ikhsan, Muhammad (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
The Community Service Program (PKM) titled " Sentuhan Alami dalam Fashion: Membuat Ecoprint Rebus dengan Daun dan Bunga " was conducted at SMP Negeri 6 Banda Aceh, aiming to introduce the ecoprint technique to teachers and students. Ecoprint is an eco-friendly fabric dyeing method that utilizes natural materials such as leaves and flowers to create artistic patterns. This program included theoretical sessions, hands-on practice, and reflective discussions. The results demonstrated that both teachers and students successfully understood and applied the ecoprint technique. In addition to enhancing creativity and teamwork skills, the program fostered environmental awareness among participants. The resulting ecoprint products showcased unique aesthetics and sustainability values, creating opportunities for potential entrepreneurial activities. Thus, this community service made a significant positive impact, both in learning aspects and environmental preservation.